Characteristics of the active-layer under the China-Russia Crude Oil pipeline - Serban, M; Li, GY; Serban, RD; Wang, F; Fedorov, A; Vera, S; Cao, YP; Chen, PC; Wang, W (Journal of Mountain Science, 2021)
Active layer is a key component for permafrost environment studies as many subsurface biological, biogeochemical, ecological, and pedogenic activities prevail in this layer. This study focuses on active layer temperature monitoring in an area with sporadic permafrost at two adjacent sites along China-Russia Crude Oil Pipeline (CRCOP), North-East China. Site T1 is located in disturbed ground on the right-of-way (on-ROW) 2 m away from the center of the oil pipeline. T2 is located in a natural and undisturbed site, around 16.6 m off-ROW. Our objective was to study seasonal variability of the active layer depth and thermal regime from October 2017 to September 2018. The monitoring sites consist of soil temperature probes arranged in a vertical array at different depths at both sites. The following parameters were computed: number of isothermal days (ID), freezing days (FD), thawing days (TD), freezing degree days (FDD), thawing degree days (TDD), number of freeze-thaw days (FTD). The mean air temperature in the monitoring period reached - 3.2 degrees C. The temperature profile indicates that the maximum active layer thickness observed during the study period was 10 m at T1 and 2 m at T2. The majority of the soil temperatures were above or close to 0 degrees C, resulting in great values of TDD, especially in the first 4 m depth. TDD for T1 were predominant and ranged between 600-1160 degrees C center dot days (0-4 m depth) reflecting the influence of oil temperature from the pipeline. In T2 borehole FDD were predominant for all the soil layer depths resulting in less permafrost degradation. This comparison emphasizes the significant influence of vegetation removal and the dispersed heat from the pipeline on the active layer thickness.